Implementasi Psikologi Pendidikan Terhadap Mutu Belajar Generasi Milenial - Eran Wandani; Ihsan Sanusi; Neng Shufi Sufhia (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The world of the younger generation is full of joy and uniqueness. In all aspects of adolescent development, puberty is a phase full of anxiety. This phase of physical growth is an early sign of adolescent growth followed by a period of adaptation to interpersonal relationships and the wider social environment. The purpose of this research is to explore the application of psychology in improving the quality of learning for the millennial generation. The method used in this research is literature review, in which the research approach is based on the opinions of experts and the results of previous research on educational psychology and millennial youth. From the results of this study, it can be concluded that as a teacher, educators must understand various aspects of student behavior and individuals related to their duties, comprehensively. This will assist educators in carrying out their duties and responsibilities effectively, which will ultimately make a real contribution to the goals of education in schools. By understanding the characteristics of students, teachers can wisely prepare the learning environment, carry out an effective teaching-learning process, even in giving assessments.